A novel dark resonance energy transfer-based fluorescent probe with large Stokes shift for the detection of pH and its imaging application. (October 2020) - Wang, Xiuji; Zhang, Lijian; Li, Qin; Gao, Yihua
Abstract: Herein, we design and synthesize a pH-dependent turn-on fluorescent probe based on the dark resonance energy transfer (DRET) strategy. A silacyclopentadiene (silole) derivative with aggregation-induced emission (AIE) properties is selected as dark energy donor and a rhodamine B derivative with spirocyclic structure as energy acceptor. Attributed to the non-emissive character of silole in solution, fluorescence leakage from the donor is eliminated. Binding with H + turns on the DRET process and energy of donor is converted to the acceptor's fluorescence output before non-radiative decay. The probe responds to pH variation from 2.75 to 5 in buffer solutions with a Stokes shift up to 220 nm. In addition, imaging experiments suggest that the probe is capable of determining pH fluctuations in live cells with good cell membrane permeability and low cytotoxicity. Graphical abstract: Image 1 Highlights: A fluorescent probe for pH detection was designed and synthesized based on the dark resonance energy transfer. Energy was transferred from dark silole donor to rhodamine acceptor with large Stokes shift. This probe could be used to detect pH vibration in live cells.